Novel pleiotropic risk loci for melanoma and nevus density implicate multiple biological pathways. Issue 1 (December 2018) - Duffy, David; Zhu, Gu; Li, Xin; Sanna, Marianna; Iles, Mark; Jacobs, Leonie; Evans, David; Yazar, Seyhan; Beesley, Jonathan; Law, Matthew; Kraft, Peter; Visconti, Alessia; et al.
Abstract The total number of acquired melanocytic nevi on the skin is strongly correlated with melanoma risk. Here we report a meta-analysis of 11 nevus GWAS from Australia, Netherlands, UK, and USA comprising 52, 506 individuals. We confirm known loci includingMTAP, PLA2G6, andIRF4, and detect novel SNPs inKITLG and a region of 9q32. In a bivariate analysis combining the nevus results with a recent melanoma GWAS meta-analysis (12, 874 cases, 23, 203 controls), SNPs nearGPRC5A, CYP1B1, PPARGC1B, HDAC4, FAM208B, DOCK8, andSYNE2 reached global significance, and other loci, includingMIR146A andOBFC1, reached a suggestive level. Overall, we conclude that most nevus genes affect melanoma risk (KITLG an exception), while many melanoma risk loci do not alter nevus count. For example, variants inTERC andOBFC1 affect both traits, but other telomere length maintenance genes seem to affect melanoma risk only. Our findings implicate multiple pathways in nevogenesis. Melanocytic nevus count is associated with melanoma risk. In this study, a meta-analysis of 11 nevus GWAS studies identifies novel SNPs in KITLG and 9q32, and bivariate analysis with melanoma GWAS meta-analysis reveals that most nevus genes affect melanoma risk, while melanoma risk loci do not alter the nevus count.